2018
DOI: 10.1038/s41431-017-0053-7
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of Hirschsprung disease detects a novel low-frequency variant at the RET locus

Abstract: Hirschsprung disease (HSCR) is a congenital disorder with a population incidence of ~1/5000 live births, defined by an absence of enteric ganglia along variable lengths of the colon. HSCR genome-wide association studies (GWAS) have found common associated variants at RET, SEMA3, and NRG1, but they still fail to explain all of its heritability. To enhance gene discovery, we performed a GWAS of 170 cases identified from the Danish nationwide pathology registry with 4717 controls, based on 6.2 million variants im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 49 publications
(63 reference statements)
1
23
0
Order By: Relevance
“…More recently, another HSCR GWAS of Caucasians was published. It confirmed RET and SMEA3 as being associated with HSCR in a Danish cohort, and additionally reported a novel low‐frequency variant (rs144432435) of RET …”
Section: Genome‐wide Association Study and Hscrmentioning
confidence: 53%
“…More recently, another HSCR GWAS of Caucasians was published. It confirmed RET and SMEA3 as being associated with HSCR in a Danish cohort, and additionally reported a novel low‐frequency variant (rs144432435) of RET …”
Section: Genome‐wide Association Study and Hscrmentioning
confidence: 53%
“…It is well known that genetic factors play an essential role in the development of HSCR, with RET as the major risk gene, as genome-wide association studies (GWASs) using single nucleotide polymorphism (SNP) chip revealed that RET, SEMA3, and NRG1 were associated with HSCR, which was also confirmed in subsequent independent studies (Garcia- Barcelo et al, 2009;Kim et al, 2014;Jiang et al, 2015;Fadista et al, 2018). Earlier studies adapting whole genome or exome sequencing strategies also revealed new risk variants with high penetrance.…”
Section: Introductionmentioning
confidence: 81%
“…In the past few years, the identification of novel susceptibility genes and variants for HSCR was based on the use of GWAS,GWES 20,25,[38][39][40][154][155][156][157][158][159][160][161] and next-generation sequencing (NGS) approaches. [162][163][164][165][166][167][168][169][170] All of them have fairly improved our knowledge about the genetic background of the disease.…”
Section: New Approachesmentioning
confidence: 99%